Pembuatan Bioetanol Dari Limbah Tongkol Jagung Menggunakan Proses Simultaneous Sacharificatian and Fermentation (SSF) Dengan Variasi Konsentrasi Enzim Dan Waktu Fermentasi - Elgina May Lestari; Elvi Yenie; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
One of energy source alternative that can be used as a substitute for fossil fuel-based energy, is bioethanol. Bioethanol is biochemistry fluid from fermentation process of sugars by using microorganism. The raw material of bioethanol production is very diverse, like corn cob. Corn cob can be used as raw material for bioethanol production because contain of cellulose. This study aims to make bioethanol from corn cob with Sacharificatian Simultaneous and Fermentation (SSF) process with cellulase enzyme variation are 3%, 5%, 7%, 9%, and 11% v/v substrate and fermentation time are 3, 4, and 5 days. From the research is obtained the highest bioethanol concentration is 5% on the addition of cellulase enzymes 11% v/v substrate with 3 days fermentation time.Keyword: Bioethanol, Corn cob, Cellulase, SSF